Decomposing the gender wage-gap in the hospitality industry: a quantile approach - Campos-Soria, Juan Antonio; Marfil-Cotilla, Marina (Congreso ASEPELT-2021, 2021)
This paper discusses the factors that determine the wage differences between men and women in the Spanish hospitality industry across the wage distribution. In general, previous studies have analysed the gender wage gap from a global perspective, without taking into account the heterogeneity across the wage distribution. It has also shown that there are factors such as vertical segregation, labour mobility or “glass ceilings” that it have a special impact on specific occupational groups (Burguess, 2003; Skalpe, 2007; Baum, 2013; Carvalho, Costa, Lykke, Torres, 2019); thus, it would be of interest to the state of the art to look more closely at the main factors that determining the gender wage gap, and in particular its discriminatory component across wage distribution. Using matched employer-employee data from a sample of 4,991 workers, we propose different wage decompositions based on quantile regressions, under the assumption of equal and different returns. Our results show that the wage advantage of men presents an increasing profile along the wage distribution, being particularly relevant in the higher wage group. Furthermore, its shown the existence of a high degree of gender wage discrimination in the sector, although it is decreasing across the wage distribution. Differences in returns of human capital and vertical segregation are the main causes that explain the discriminatory component. In addition, there is evidence of the possible existence of the so-called “glass ceiling”.
Keywords: Discriminación sexual; Turismo - Personal; Gender wage gap; Quantile approach; Tourism